1994
DOI: 10.1213/00000539-199403000-00002
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Multicenter, Randomized Controlled Trial on the Safety and Efficacy of Acadesine in Patients Undergoing Coronary Artery Bypass Graft Surgery

Abstract: Acadesine (5-amino-4-imidazole carboxamide riboside) is a purine nucleoside analog that has been shown in animals to reduce myocardial ischemic injury by selectively increasing the availability of adenosine in ischemic tissues. Because patients undergoing coronary artery bypass graft (CABG) surgery are especially vulnerable to developing myocardial ischemia, we investigated whether perioperative use of this adenosine-regulating drug with potential anti-ischemic properties could modify the incidence and severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Finally, several clinical trials, designed to evaluate the antiinflammatory effect of AICAR in preventing the adverse effects of a coronary artery bypass graft, demonstrated that this drug was well tolerated in humans, with no apparent side effects (35,36). Therefore, although additional work is required to understand the molecular mechanism by which AICAR promotes the development of T cells endowed with B cell helper capacity, the present approach may pave the way to novel and safer adjuvants to promote humoral responses in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, several clinical trials, designed to evaluate the antiinflammatory effect of AICAR in preventing the adverse effects of a coronary artery bypass graft, demonstrated that this drug was well tolerated in humans, with no apparent side effects (35,36). Therefore, although additional work is required to understand the molecular mechanism by which AICAR promotes the development of T cells endowed with B cell helper capacity, the present approach may pave the way to novel and safer adjuvants to promote humoral responses in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this compound has been shown to cause a significant decrease in intracellular ATP levels in several human and murine cell lines (32)(33)(34). Despite the lack of precise information concerning its mode of action, AICAR has been used extensively in animals and human clinical studies as a putative agent thought to protect the heart, lung, and small intestine against ischemic damage (35,36), and the safety, tolerance, and pharmacokinetics of this compound are well described (37). The ability of AICAR to increase T cell-dependent humoral responses in vivo therefore was evaluated.…”
Section: Aicar Augments Humoral Responses In Vivomentioning
confidence: 99%
“…Patients with AICAR orally or intravenously administrated during clinical trials revealed that the bioavailability of AICAR is <5% and its half-life is just ∼2 h [121]. More importantly, patients treated with AICAR have adverse side effects that they exhibit significant increases in the production of lactic and uric acid [121][122][123]. Although AICAR is an important research tool for investigating the effects of AMPK activation and mTOR inhibition on tumorigenesis, it is obviously not suitable for clinical use yet.…”
Section: Activators Of Ampk That Interfere Cellular Energy Homeostasismentioning
confidence: 99%
“…Schoenberg et al [99] showed that acadesine 5-amino-4-imidazolecarboxamide riboside, a purine nucleoside analogue, in creases the availability of adenosine in the intestinal tis sue and inhibits the accumulation of leukocytes in the mucosal layer of the postischemic intestine. Since acade sine is a safe and well-tolerated compound in healthy young men and already used during cardiac bypass sur gery in order to protect the myocardium, 5-amino-4-imidazolecarboxamide riboside seems to be an interesting option for the treatment of postischemic tissue damage [100,101].…”
Section: Repcrfusion Injurymentioning
confidence: 99%